Preparation and Evaluation of Performance of Lime Saccharate for Improving Juice Clarification: The Case of Wonji Sugar Factory - Tesfaye Nemera (ASTU, 2020)
In this study, lime saccharate, has been prepared, the efficiency of lime sacharate was also evaluated, further its performance has been compared with milk of lime (MOL). For the preparation of lime saccharate, milk of lime, Ca(OH)2 of 15 degree Baume was used with evaporator syrup collected from Wonji Shoa Sugar factory. Nine mixed juice samples were taken from weighed mixed juice tank and pretreated so as to be used for settling and mud volume tests. The required response variables color, turbidity and CaO content were determined for the clarified juice obtained for each treatment replicated twice. The experiment was arranged using RCBD (Randomized complete block Design). Then, the data obtained from the comparative experiments were subjected to statistical analysis using SAS statistical software. The result of the experiment has shown that the settling rate and CJ purity have shown little variation in quality parameters at 5% level of significance. As observed in the data in the defecation process, lime saccharate treated clear juice gave better results for mud volume, ICUMSA color, CaO content, and CJ turbidity compared to the milk of lime treated clear juice. The work here presented a solution to the existing juice clarification problems by proving that the use of lime saccharate (SACCH) instead of the conventional milk of lime (MOL), during clarification of sugarcane juice, which can improve turbid particle removal, improve clear juice clarity, reduce calcium oxide content in clear juice and be used as a tool by sugar processors to reduce expensive sucrose losses and scaling in evaporators.
Keywords: Lime saccharate, Juice Clarification, Flocculation, Clear juice.